Formulation and Evaluation of Captopril Mouth Dissolving Film: A Recent Study - Iswariya, V. T.; Deepika, P.; Battu, Sowjanya (Current Aspects in Pharmaceutical Research and Development Vol. 7, 2022)
Now a day's fast dissolving films are preferred over conventional tablets and capsules for masking the taste of bitter drugs to increase the patient compliance. Fast dissolving films consist of a very thin oral strip which dissolves in less than one minute when placed on the tongue. The goal of this research is to develop captopril mouth dissolving films and evaluate the impact of various formulation factors on the physical and mechanical properties of the films, as well as drug release behaviour. In different grades, hydroxypropyl methyl cellulose (HPMC E15 and K4M) was employed as the film forming polymer. The various manufacturing techniques for the preparation of films have also been detailed in the review. Formulation disintegration times were determined to be in the range of (52 2.5 to 125.6 2.02 s). Formula F2 had the fastest disintegration time in vitro (52 2.5 s) and was determined to be acceptable for film production with ideal physicochemical qualities, faster disintegration, and optimal in vitro release. It may be concluded that the solvent casting approach can be used to make captopril mouth dissolving films with a higher dissolution rate and greater patient compliance.